Developing Android-Based English Folktales Learning Materials to Develop Communication Skills of Primary School Students - Kadek Yunita Adriyanti; Made Hery Santosa; G.A.P Suprianti (Cetta: Jurnal Ilmu Pendidikan, 2022)
Both teacher and students faced difficulties in teaching and learning English during remote learning and they need English learning materials which can be easily accessed during learning from home. This study aimed at developing android-based English Folktales learning materials to promote primary school students’ communication skills. This research applied Design and Development (D&D) method proposed by Richey and Klein (2007) which underwent four stages namely; 1) Analysis, 2) Design, 3) Development, and 4) Evaluation. The research subjects were an English teacher and sixth graders of SDN 1 Banjar Jawa in the academic year of 2020/2021, Bali. The research instruments used questionnaires and interview guide. The results showed that digital folktales application as the product was developed in the form of android package kit (APK) file using Microsoft Office Power Point, iSpring, and APK Builder Pro. It provided 9 Indonesian folktales and 8 follow-up learning activities. The product was tested and evaluated by a technology expert and an EFL learning expert. digital folktales application has an excellent quality as an android-based English learning material. Thus, the digital folktales application was beneficial for students and teacher as English learning material to develop communication skills.